South-South education relations - Muhr, T.; Azevedo, M. L. N. (Routledge Handbook of South-South Relations, 2019)
While scholarly interest in South–South cooperation (SSC) has substantially grown over the past decade, South–South education relations have received only scant attention in the Anglophone academic literatures on SSC, international development and international and comparative education. This chapter adopts an historical and global approach to this topic in an effort to contribute to closing this research gap. The chapter unfolds as follows: the first section introduces the concepts of ‘the South’ and ‘South–South cooperation’, counter-posed with practices of ‘triangular collaboration’ and ‘best practice transfer’. On this basis, the second section conducts a critical review of existing South–South education cooperation literatures. Framed by these discussions, two case studies of contemporary South–South education relations are presented: the ¡Yo, Sí Puedo! (Sure, I Can!) global literacy campaign promoted by the governments of the Republic of Cuba and the Bolivarian Republic of Venezuela; and the education cooperation agenda of the so-called BRICS. The conclusion resumes the question of whether South–South education cooperation simply represents ‘best practice transfer’ or Third World solidarity for global transformation, while proposals for a future research agenda are developed.